Vers une compréhension de la construction des gestuelles avec l’expérience : le cas des « tôliers » d’une entreprise automobile - Karine Chassaing (Perspectives Interdisciplinaires sur le Travail et la Santé)
The objective of this study conducted in an automobile assembly plant is to describe the construction of gestures developed with experience by operators in the sheet metal department. Observations at workstations and interviews with workers revealed the dynamics of the development of sheet metal workers’ actions during their work. The question is to reconstruct the history of one action, that is, to identify the determinants of the work strategies according to each one’s job history and life history. The results show that the operators develop different working techniques that are based, nonetheless, on common principles. These principles govern the use of the body at work, such as : avoiding pain or trying to reduce it, seeking balance in the body, distributing force to different body areas. Experience with pain associated with experience with effective/ineffective, efficient/inefficient gestures was developed over time. These principles came from different types of experience, such as professional experience : experience in production line work, previous jobs ; life experience : sports, relationship with doctors ; experience with others’ work. With this identification of operators’ logic, it is possible to question the prescription system for gestures currently adopted by the company in question, a system that tends to want to standardize practices in order to improve quality and productivity.